Conversion of dried aspergillus candidus mycelia grown on waste whey to biodiesel by in situ acid transesterification - Kakkad, Hardik; Khot, Mahesh; Smita S. Zinjarde; RaviKumar, Ameeta; Kumar, V. Ravi; Kulkarni, B. D. (Bioresource Technology, 2015)
This study reports optimization of the transesterification reaction step on dried biomass of an oleaginous fungus Aspergillus candidus grown on agro-dairy waste, whey. Acid catalyzed transesterification was performed and variables affecting esterification, viz., catalyst methanol and chloroform concentrations, temperature, time, and biomass were investigated. Statistical optimization of the transesterification reaction using Plackett-Burman Design showed biomass to be the predominant factor with a 12.5-fold increase in total FAME from 25.6 to 320 mg. Studies indicate that the transesterification efficiency in terms of conversion is favored by employing lower biomass loadings. A. candidus exhibited FAME profiles containing desirable saturated (30.2%), monounsaturated (31.5%) and polyunsaturated methyl esters (38.3%). The predicted and experimentally determined biodiesel properties (density, kinematic viscosity, iodine value, cetane number, TAN, water content, total and free glycerol) were in accordance with international (ASTM D6751, EN 14214) and national (IS 15607) standards. (C) 2015 Published by Elsevier Ltd.
Keywords: Aspergillus candidus; Biodiesel; In situ acid transesterification; Plackett-Burman Design; Whey

Methyl esters of fungal biomass-derived lipids produced via solid-state fermentation of sugarcane bagasse and assessment as a blend component in diesel fuel. - Khot, Mahesh; RaviKumar, Ameeta; Kumar, V. Ravi (Journal of the American Oil Chemists Society, 2021)